An integrative transcriptomic analysis reveals bisphenol A exposure-induced dysregulation of microRNA expression in human endometrial cells. (June 2017) - Chou, Wei-Chun; Lee, Pei-Hsuan; Tan, Yan-Yan; Lin, Ho-Chen; Yang, Chung-Wei; Chen, Kuan-Hsueh; Chuang, Chun-Yu
Abstract: Bisphenol A (BPA) are commonly used in the manufacture of polycarbonate plastics. Higher BPA exposure levels have been found in patients with endometrial hyperplasia that is one of risk factors of endometrial cancer (EC). Aberrant microRNAs (miRNAs) regulation has been observed in the development of cancer. Thus, this study investigated whether BPA exposure can disrupt miRNA regulation and its gene expression regarding to EC carcinogenic progress. Microarray experiments of miRNA and mRNA were performed in human endometrial cancer RL95-2 cells with treatment of low-to-moderate (10, 10 3 and 10 5 nM) BPA to explore the aberrant genes corresponding to human EC progression. According to the analysis of KEGG pathway and Cytoscape gene network, this study identified that BPA exposure reduced miR-149 expression to down-regulate DNA repair gene ARF6 (ADP-ribosylation factor 6) and tumor protein p53 (TP53), and up-regulate CCNE2 (cyclin E2) potentially to interrupt cell cycle. BPA also increased miR-107 to suppress hedgehog signaling factors, suppressor of fused homolog (SUFU) and GLI family zinc finger 3 (GLI3) to activate hedgehog signaling for cell proliferation underlying carcinogenesis. Furthermore, the BPA-induced cell proliferation was attenuated by transfection with miR-149 mimic and miR-107 inhibitor. These findings provided an insight into potential epigenetic mechanism of BPA exposure on the risk of endometrial carcinogenesis. Highlights: Transcriptomic analysis of mRNA and miRNA profiling for human endometrial cells in exposure to BPA. BPA reduced miR-149 in ARF6-TP53-CCNE2 pathway to interrupt cell cycle arrest. BPA decreased miR-149 to initiate migration and invasion for cancer metastasis. BPA increased miR-107 to reduce hedgehog SUFU-GLI3 signaling in DNA repair for cancer cell growth. BPA can affect miRNA regulatory pathways potentially for endometrial carcinogenesis.